Geneva Conventions at 75: Alleviating Human Suffering in Armed Conflicts - Chalisey, Krishna Chandra (NCWA Annual Journal, 2025)
The Geneva Conventions of 12 August 1949, cornerstone instruments of international humanitarian law (IHL), marked their 75th anniversary in 2024. IHL, a branch of public international law, governs situations of armed conflict - whether international or non-international. While all 196 sovereign nations have universally accepted the Geneva Conventions, violations of IHL persist, highlighting the need for improved compliance by both state and non-state armed groups. In this context, this article analyzes the continued relevance of IHL in addressing the growing number of armed conflicts worldwide. However, there remains a disparity in the rules governing non international armed conflicts (NIAC) compared to international armed conflicts (IAC), which necessitates further development. The 34th International Conference of the Red Cross and Red Crescent, held in 2024, has raised hopes for enhanced compliance with IHL. In light of the increasing prevalence of armed conflicts and the proliferation of armed groups, a concerted effort by the United Nations and humanitarian organizations is essential. For Nepal, it is advisable to take proactive steps to strengthen its IHL ratification record and contribute to global efforts to uphold these critical humanitarian standards.